The Effect of Probiotics on Gut Microbiota during the Helicobacter pylori Eradication: Randomized Controlled Trial - Oh, Bumjo; Kim, Bong-Soo; Kim, Ji Won; Kim, Jong Seung; Koh, Seong-Joon; Kim, Byeong Gwan; Lee, Kook Lae; Chun, Jongsik (Helicobacter (Cambridge, Mass.), 2016)
Background Helicobacter pylori causes chronic gastritis, gastroduodenal ulcers, and gastric cancer, and has been treated with two antibiotics (amoxicillin and clarithromycin) and proton‐pump inhibitors (PPIs). However, antibiotic treatment alters the indigenous gut microbiota to cause side effects. Therefore, the effects of probiotic supplementation on therapy have been studied. Although several studies have covered the probiotics’ effects, details about the gut microbiota changes after H. pylori eradication have not been evaluated. Therefore, we analyzed the influences of antibiotics and their combination with probiotics on the composition of the gut microbiota using high‐throughput sequencing. Methods Subjects were divided into two groups. The antibiotics group was treated with general therapy, and the probiotics group with general therapy and probiotic supplementation. Fecal samples were collected from all subjects during treatments, and the influences on gut microbiota were analyzed by 16S rRNA gene‐pyrosequencing. Results Three phyla, Firmicutes, Bacteroidetes, and Proteobacteria, were predominant in the gut microbiota of all subjects. After treatment, the relative abundances of Firmicutes were reduced, whereas those of Proteobacteria were increased in both groups. However, the changed proportions of the gut microbiota in the antibiotics group were higher than those in the probiotics group. In addition, the increase in the levels of antibiotic‐resistant bacteria was higher in the antibiotics group than in the probiotics one. Conclusion Probiotic supplementation can reduce the antibiotic‐induced alteration and imbalance of the gut microbiota composition. This effect may restrict the growth of antibiotic‐resistant bacteria in the gut and improve the H. pylori eradication success rate.